2021
DOI: 10.3390/ma14174865
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite in Oral Care Products—A Review

Abstract: Calcium phosphate compounds form the inorganic phases of our mineralised tissues such as bone and teeth, playing an important role in hard tissue engineering and regenerative medicine. In dentistry and oral care products, hydroxyapatite (HA) is a stable and biocompatible calcium phosphate with low solubility being used for various applications such as tooth remineralisation, reduction of tooth sensitivity, oral biofilm control, and tooth whitening. Clinical data on these products is limited with varied results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 68 publications
(224 reference statements)
4
50
0
1
Order By: Relevance
“…Various toothpastes with added HAP have been available for several years. Since there is a great chemical similarity of HAP with human enamel, the active ingredient HAP is supposed to adhere to the tooth surface during tooth brushing, thus forming a protective layer against bacteria and acids, and also repairing enamel areas attacked by acid [ 14 ]. However, little is known about the interaction of HAP with tooth structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various toothpastes with added HAP have been available for several years. Since there is a great chemical similarity of HAP with human enamel, the active ingredient HAP is supposed to adhere to the tooth surface during tooth brushing, thus forming a protective layer against bacteria and acids, and also repairing enamel areas attacked by acid [ 14 ]. However, little is known about the interaction of HAP with tooth structure.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, whether HAP is an agent that can affect caries, erosion, or plaque formation is currently not fully understood [ 12 ]. In the literature, some studies can be found that were able to show comparable, positive effects of HAP and fluoride in terms of remineralization and caries prevention; however, the vast majority of studies were unable to demonstrate statistically significant better remineralization features of HAP compared to fluoride [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies reported the use of γ-PGA as a nutrition supplement in dietary products for enhanced Ca 2+ solubility, explaining its role in increased calcium absorption in the small intestine [ 31 , 32 ]. Another widely available material, nano-HAp, has applications in biomedical areas such as dentistry and orthopedics, [ 33 ] owing to its excellent biocompatible, osteoconductive, and bioactive behavior [ 34 , 35 ]. The enamel has a complex structure for remodeling and comprises basic building blocks of ~20–40 nm HAp nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…• Hydroxyapatite can bind to microorganisms by interacting with the bacterial adhesin thus agglutinating the microorganism. 45 Fluoride Bioglass may be recommended for treatment of dentin hypersensitivity. It can be used daily by individuals with a compromised periodontal status and individuals with a compromised enamel surface.…”
Section: To Treat Dentin Hypersensitivitymentioning
confidence: 99%